Recent Progress of Adenosine Receptor Modulators in the Development of Anticancer Chemotherapeutic Agents - Marwein, Sarapynbiang; Mishra, Bijayashree; De, Utpal C.; Acharya, Pratap C. (Current Pharmaceutical Design, 2019)
Increased risks of peripheral toxicity and undesired adverse effects associated with chemotherapeutic agents are the major medical hurdles in cancer treatment that worsen the quality of life of cancer patients. Although several novel and target-specific anticancer agents have been discovered in the recent past, none of them have proved to be effective in the management of metastatic tumor. Therefore, there is a continuous effort for the discovery of safer and effective cancer chemotherapeutic agent. Adenosine receptors have been identified as an important target to combat cancer because of their inherent role in the antitumor process. The antitumor property of the adenosine receptor is primarily attributed to their inherited immune response against the tumors. These findings have opened a new chapter in the anticancer drug discovery through adenosine receptor-mediated immunomodulation. This review broadly outlines the biological mechanism of adenosine receptors in mediating the selective cytotoxicity as well as the discovery of various classes of adenosine receptor modulators in the effective management of solid tumors.
Keywords: pro-tumoral and anti-tumoral effects